Self-Efficacy of Adolescents in Coastal Areas: A Descriptive Study of Vocational School Students - Yusuf Darmansyah; Maria Komariah; Kurniawan Kurniawan (Indonesian Journal of Global Health Research, 2025)
Self-efficacy, as a trust in self-abilities, plays a significant role in career planning and the students readiness to face competition in the workforce. High unemployment rate among vocational high school graduates makes this issue important to investigate. This study aims to describe students self-efficacy and factors influencing their trust in themselves. This research used a descriptive quantitative method with a cross-sectional approach. The population is 12th-grade students at vocational high school (SMK) Putera Pangandaran, with a sample of 151 students selected through total sampling. Data were collected using a self-efficacy scale questionnaire for vocational school students (r0.42-0.82, (Cronbach alpha) a0.94) via Google Form and analyzed univariately. The results revealed that the majority of respondents had high self-efficacy, with 99.2% categorized as high in the domains of level and generality, and 91.6% in the domain of strength. The high self-efficacy levels were influenced by the coastal areas and experiences, skills, also knowledge gained during internships. This study concluded that most respondents have high self-efficacy.